2018
DOI: 10.1111/dme.13618
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects on the risk of macrovascular and microvascular events of antihyperglycemic drugs that enhance sodium excretion and lower blood pressure

Abstract: Three classes of anti-hyperglycaemic medications are distinguished by their urinary sodium excretion-enhancing and blood pressure-lowering actions: long-acting glucagon-like peptide-1 receptor agonists, dipeptidyl peptidase-4 inhibitors and sodium-glucose co-transporter-2 inhibitors. Yet, these drugs exert different effects on macrovascular risk. Glucagon-like peptide-1 receptor agonists reduce atherosclerotic thromboembolic events, but have little effect on heart failure; sodium-glucose co-transporter-2 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…Several other diabetic therapies, including GLC-like peptide-1 agonists 37, 38, dipeptidyl peptidase 4 inhibition (39), and sodium glucose cotransporter 2 inhibitors 40, 41, have demonstrated various degrees of cardiovascular benefits along with ameliorated metabolic defects in glucose homeostasis. Yet, not all glucose-lowering therapies have such significant cardiovascular protective effects as sodium glucose cotransporter 2 inhibition 42, 43, 44, 45, 46. It is also unclear if these therapies will be efficacious for common forms of heart failure without the confounding metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Several other diabetic therapies, including GLC-like peptide-1 agonists 37, 38, dipeptidyl peptidase 4 inhibition (39), and sodium glucose cotransporter 2 inhibitors 40, 41, have demonstrated various degrees of cardiovascular benefits along with ameliorated metabolic defects in glucose homeostasis. Yet, not all glucose-lowering therapies have such significant cardiovascular protective effects as sodium glucose cotransporter 2 inhibition 42, 43, 44, 45, 46. It is also unclear if these therapies will be efficacious for common forms of heart failure without the confounding metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been described that treatment with empagliflozin decreases NHE3 expression in the kidneys of diabetic otsuka long-evans tokushima Fatty (OLETF) rats, as well as the expression of Na + -K + -2Cl − cotransporters and epithelial Na + channels, when compared to untreated littermates, suggesting that SGLT2 modulates the Na + reabsorption of several tubular transporters [47]. GLP-1RAs only seem to decrease NHE3 activity [48,49,50], a fact that would explain the difference in the natriuretic potential of these two drugs [51]. It is unclear whether GLP-1RAs inhibit NHE3 activity through interaction with the GLP-1 receptor or extrarenal mechanisms, such as the renin–angiotensin system or atrial natriuretic peptide modulation [52,53].…”
Section: Potential Nephroprotective Mechanisms Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…1,4 The literature on renal outcomes associated with SGLT-2is is conflicting. Some studies have indicated that SGLT-2is slow the progression of chronic kidney disease (CKD), 5,6 reduce the annual decline in estimated glomerular filtration rate (eGFR) 7,8 and reduce the development of AKI 9 ; however, others have shown a decline, or an initial decline followed by an improvement, in renal function. [10][11][12][13] This question is important, as with an ever-growing array of treatment options for type 2 diabetes, selecting the right medication and avoiding adverse events are important.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on renal outcomes associated with SGLT‐2is is conflicting. Some studies have indicated that SGLT‐2is slow the progression of chronic kidney disease (CKD), 5,6 reduce the annual decline in estimated glomerular filtration rate (eGFR) 7,8 and reduce the development of AKI 9 ; however, others have shown a decline, or an initial decline followed by an improvement, in renal function 10–13 …”
Section: Introductionmentioning
confidence: 99%